Significance of oral health education in maintaining oral health - Johnson John Omale; Balarabe Musa Hussain; Chijioke Peter Nwosu; Oluchi Ann Olofin; Scholastica Chidi Okoli; Angela N. Ohadoma (Orapuh, Inc., 2021)
This article is a qualitative review of the variables that are significant to maintaining oral health through oral health education. The consequences of lack of oral health awareness were also addressed by reviewing the story of a village girl with poor oral health. Oral tissues are vulnerable to disease because of their intimate relationship with the external environment, and they are also subject to mechanical, chemical, and bacteria invasion. The oral cavity must be healthy to prevent the occurrence of common oral diseases such as dental caries and periodontal disease. The mouth is the major gateway to the body; thus, whatever affects oral health may also affect general health. There is strong evidence that oral health knowledge is related to better oral health practice. This is because giving adequate information and motivating an individual will improve their practice of oral health measures such as regular tooth brushing, flossing, eating fewer sucrose diets, etc. Oral health knowledge can only be acquired through oral health education. Oral health education includes the dissemination of information to promote awareness and knowledge of oral health problems and self-care preventive measures through community and school-based education.